A Comparison of Yogurt and Probiotic Supplements Effects on the Hardness of Tooth Enamel: An In vitro Study: Perbandingan Pengaruh Yogurt dan Suplemen Probiotik terhadap Kekerasan Enamel Gigi: Studi in Vitro - Primasari, Ameta; Alfarizi, Tengku Rizky; Minasari, Minasari; Yendriwati, Yendriwati; Hidayati, Rizka (TALENTA, 2022)
The demineralization of tooth enamel, which can be triggered by acidic foods and drinks at pH < 5.5, can initiate dental caries. Yogurt and probiotic supplements are drinks that are often consumed to help digestive function and improve the immune system. However, both drinks have a low pH, thereby, a long time of consumption can trigger the demineralization process. This study aims to evaluate the enamel hardness after applying yogurt and probiotic supplements, which was carried out experimentally in a laboratory with a one-group post-test design. The sample used is 9 human maxillary premolars in each treatment group. The treatment group comprises the test material, such as yogurt and probiotic supplements, as well as one control group with artificial saliva. Dental samples were immersed in the test material for 96 hours, and the enamel hardness level was measured with a Micro Vickers Hardness tester. The T-paired test showed that soaking with yogurt does not significantly affect the hardness of the enamel, as indicated by a p-value of 0.016. However, the effect was significant in probiotic supplements, with p=0.004. The results showed that soaking with yogurt was not significantly different from probiotic supplements in reducing enamel hardness, as evidenced by the Post Hoc (LSD) test (p=0.464). Conclusively, yogurt decreased enamel hardness less than probiotic supplements.